An empirical study analysing the dynamics of two International Strategic Alliances in the Indian hotel industry - Rathore, Abhijeet (2009)
This report undertakes a significant study in the field of Indian hotel industry, which has witnessed some major strategic co-marketing alliances with renowned International hospitality players that have become more prominent especially after the liberalisation of Indian economy in early nineties. The rationale behind this report is to critically examine the dynamics of two well known international joint ventures namely, Hotel Leelaventure-Kempinski Hotels and East India Hotels limited - Hilton International. In such a scenario, the primary objective of multinationals is the quest for potential future markets and on the other hand, domestic firms look for international visibility in terms of brand building.